Cultivating the Family Studies Terrain: A Synthesis of Qualitative Conceptual Articles. Issue 2 (June 2014) - Sharp, Elizabeth; Zvonkovic, Anisa; Humble, Áine M.; Elise Radina, M.
<x xml:space="preserve">Abstract</x> With the intent of cultivating the family studies field, we review and synthesize conceptual discussions of qualitative work published since 1985 in the field of family studies. We critically examine the extent to which conditions in the field offer richness and sustainability for qualitative scholarship. We classify discussions by 3 overarching patterns: (a) appreciating, (b) expanding, and (c) improving qualitative research. Using these patterns as a framework, we encourage scholars to spend less attention appreciating qualitative research and calling for expansion. We recommend instead more critical engagement, greater synthesis, and contemplation of fertile issues accompanying the vast (existing and potential) territory of qualitative research in family studies.